Inovação das práticas de competência informacional com o uso de metodologias ativas de ensino-aprendizagem em bibliotecas universitárias - Maia, Cristina Marchetti (2020)
Libraries play a fundamental pedagogical role in teaching information competences in individuals, by providing mechanisms for the development of competences aimed at the awareness of information-related processes and the construction of new knowledge through the incorporation of concepts, as well as the mastery of traditional information seeking techniques. Such skills include the use of digital tools that take into consideration professionals´ and users´ rights and duties; a commitment to the cultural collective; the development of an understanding of the current information scenario and the constant transformations that occur within it. The research we describe in this chapter aimed to contextualize and comprehend Active Methodology approaches to teaching and learning, seeking a critical reflection regarding their use in information literacy initiatives in HE institutions. The hypothesis is the Information Literacy, when based on principles of active teaching and learning and as an integral part of the pedagogical HE environment, can deliver positive results and ensure greater effectiveness in student learning. The research we describe here is of a descriptive-exploratory nature. The approach for data collection was that of bibliographic research, followed by a structured content analysis of the selected retrieved documents. Twenty-three publications were selected for analysis between 2015 and 2019. The active methodologies discussed in these retrieved papers were: the Flipped Classroom, Inquiry Based Learning, Peer Instruction, Activity Based Learning, Project Based Learning, Problem Based Learning, Backward Design, Cephalonian Method, Minute Paper and Storytelling. The Flipped Classroom was the most-frequently used method and the only one that was used alongside other learning techniques. As to the use of resources and Digital Information and Communication Technologies (DICT) used in the application of different active methodologies, the use of videos and tutorials predominated. In general, the satisfaction levels among students were good in the groups in which the methodologies were applied and the positive points highlighted were: increased interest from the students during the sessions; improved interaction and collaboration between colleagues and the instructor; greater student involvement during the dynamics, as well as increasing the confidence level to perform the proposed activities, such as when performing the research tasks. The exception was one Activity Based Learning report which clearly stated that the active learning mode did not achieve the expected results compared to the use of lectures. It is our hope that the discussions and proposals that we present and systematize in this study will instigate library professionals to rethink their pedagogical approaches towards creating and running information literacy programmes in HE environments, by to underpin their professional practice about teaching methodologies promoted by librarians.